Lithium vs. valproate vs. olanzapine vs. quetiapine as maintenance monotherapy for bipolar disorder: a population-based UK cohort study using electronic health records. - Hayes, J; Marston, L; Walters, K; Geddes, J; King, M; Osborn, D (Wiley, 2016)
It is unclear which maintenance treatment for bipolar disorder is superior in clinical practice. Randomized controlled head-to-head trials of available drugs either do not exist or are inconclusive. We aimed to compare rates of monotherapy treatment failure in individuals prescribed lithium, valproate, olanzapine or quetiapine by a population-based cohort study using electronic health records. 5,089 patients with bipolar disorder were prescribed lithium (N=1,505), valproate (N=1,173) olanzapine (N=1,366) or quetiapine (N=1,075) as monotherapy. Treatment failure was defined as time to stopping medication or add-on of another mood stabilizer, antipsychotic, antidepressant or benzodiazepine. In unadjusted analyses, the duration of successful monotherapy was longest in individuals treated with lithium. Treatment failure had occurred in 75% of those prescribed lithium by 2.05 years (95% CI: 1.63-2.51), compared to 0.76 years (95% CI: 0.64-0.84) for those prescribed quetiapine, 0.98 years (95% CI: 0.84-1.18) for those prescribed valproate, and 1.13 years for those prescribed olanzapine (95% CI: 1.00-1.31). Lithium's superiority remained in a propensity score matched analysis; when treatment failure was defined as stopping medication or add-on of a mood stabilizer or antipsychotic; and when treatment failure was restricted to more than three months after commencing the study drug. Lithium appears to be more successful as monotherapy maintenance treatment than valproate, olanzapine or quetiapine. Lithium is often avoided because of its side effect profile, but alternative treatments may reduce the time to being prescribed more than one drug, with potential additive side effects of these treatments.